2014
DOI: 10.1371/journal.pone.0091504
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory-Based Evaluation of Four Rapid Point-of-Care Tests for Syphilis

Abstract: BackgroundSyphilis point-of-care tests may reduce morbidity and ongoing transmission by increasing the proportion of people rapidly treated. Syphilis stage and co-infection with HIV may influence test performance. We evaluated four commercially available syphilis point-of-care devices in a head-to-head comparison using sera from laboratories in Australia.MethodsPoint-of-care tests were evaluated using sera stored at Sydney and Melbourne laboratories. Sensitivity and specificity were calculated by standard meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
4
24
1
Order By: Relevance
“…Results consistent with those found in the present study (100.0%) were reported by Lien et al 16 Hernández-Trejo et al 17 and Siedner et al 18 Other authors reported low sensitivity values when using finger-prick, whole blood samples as 88.0%,18 91.8%,19 85.7%20 and 97.3% 21. A multicentre clinic-based study performed by Mabey et al 22 also found low sensitivity in Tanzania (59.6%), Brazil (88.5%), China (81.9%) and Haiti (72.5%) 22…”
Section: Discussionsupporting
confidence: 93%
“…Results consistent with those found in the present study (100.0%) were reported by Lien et al 16 Hernández-Trejo et al 17 and Siedner et al 18 Other authors reported low sensitivity values when using finger-prick, whole blood samples as 88.0%,18 91.8%,19 85.7%20 and 97.3% 21. A multicentre clinic-based study performed by Mabey et al 22 also found low sensitivity in Tanzania (59.6%), Brazil (88.5%), China (81.9%) and Haiti (72.5%) 22…”
Section: Discussionsupporting
confidence: 93%
“…The independent variables included gender (male or female), age (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), 36-45 and 46-65 years), education level (complete or incomplete primary or secondary school), residence region (from the seven major geographical regions of the state: Florianópolis, Extremo Oeste, Meio Oeste, Planalto Norte, Sul, Vale do Itajaí and Planalto Serrano) and previous blood donation status (never, within previous 12 months or more than 12 months ago). This model allowed for an estimation of the syphilis infection probability among those donors who did not return for follow-up testing, despite a reactive screening test result.…”
Section: Methodsmentioning
confidence: 99%
“…False-negative test results are more likely to occur with treponemal tests compared with VDRL tests in the early phase (2-3 weeks) of infection, whereas the opposite is true for the later stages of infection 29 . Most non-treponemal tests are less sensitive in patients with primary syphilis than in those with secondary syphilis 30 . Both false-positive and false-negative test results may bias the prevalence estimates; however, they are often diffi cult to quantify in blood bank settings.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…The meta-analysis found that the Determine rapid test (Abbott Diagnostics, United Kingdom) using a serum sample had the best sensitivity (92.03%; 95% confidence interval [CI], 87.2% to 95.8%) and that Syphicheck (Qualpro, India) had the best specificity (99.4%; 95% CI, 98.9% to 99.8%). An Australian laboratory-based study of four syphilis POCT using stored sera reported that the Determine test had the highest overall sensitivity, with significantly higher test sensitivities among high-RPR-titer (RPR Ն 1:8) tests (61). POCT results were compared to treponemal immunoassay reference test results.…”
Section: Poctmentioning
confidence: 99%